Heavy Metals in Homoeopathic Mother Tinctures – Is it a Cause for Concern? (Advancements in Homeopathic Research, 2023)
Introduction: The presence of heavy metals in higher  quantity is a cause for concern in herbal medicines.  Around 60-70% of homoeopathic medicines are  manufactured using herbs. Herbs account for even  more than 90% of the frequently used mother  tinctures. There is a possibility of heavy metals  transfer from herbs to the mother tincture during the  manufacturing process.  Objective: This study was conducted to find out the  transmission of heavy metals from herbs to mother  tinctures. Material and methods: 10 herbs have been identified  based on the literature survey for the presence of  heavy metals (lead, mercury, arsenic and cadmium).  Samples of both herbs and the mother tinctures made  from them have been studied for the presence of  heavy metals in mg/kg. Results & discussion: 8 out of 10 herbs were  found to contain heavy metals. However, none of  the homoeopathic mother tinctures prepared from  these herbs has any trace of the presence of heavy  metal. Even though mother tinctures are diluted 10  times and they may contain 1/10th of heavy metals  present in the herbs, we could not find even 1/10th of the heavy metal in the mother tincture. This could  be due to their insoluble nature in the solvents used.  Perhaps all the heavy metals have been retained into  the herbal residue. Conclusion: Heavy metals present in the studied  herbs do not transport during the manufacturing  of homoeopathic mother tinctures. Thus, these  homoeopathic mother tinctures may be considered  safe with respect to heavy metals.
Keywords: Herbs; heavy metals; mother tincture; toxicity